1985
DOI: 10.1111/j.1469-8749.1985.tb04567.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the Visual Evoked Response and Its Correlation With Visual Acuity in Preterm Infants

Abstract: SUMMARY Visual evoked responses (VERs) were elicited in 70 infants with postmenstrual ages between 30 and 39 weeks. On the basis of neurological and ultrasound examinations, 30 of the infants were classed as neurologically normal and 40 as abnormal: 26 of the latter had periventricular haemorrhage. Initially the VER consisted of a negative deflection only, and the appearance of a positive wave immediately preceding the negative deflection was taken to indicate maturation of the VER. Maturation was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Placzek et al (1985) recorded flash VEPs in 70 preterm infants, 26 of whom had evidence of a germinallayer intraventricular haemorrhage (GL-IVH) on cranial ultrasound. The major positive component P2, which is consistently present in all normal neonates from 37 weeks' gestation onwards (Placzek et al 1985), was present in over 90% of the neurologically normal infants by 35 to 36 weeks gestational age (GA), but a large proportion of infants with intraventricular haemorrhage (IVH) manifested immature flash-VEP waveforms. The authors concluded that the extent of delay in the maturation of the VEP was related to the degree of neurological insult.…”
mentioning
confidence: 99%
“…Placzek et al (1985) recorded flash VEPs in 70 preterm infants, 26 of whom had evidence of a germinallayer intraventricular haemorrhage (GL-IVH) on cranial ultrasound. The major positive component P2, which is consistently present in all normal neonates from 37 weeks' gestation onwards (Placzek et al 1985), was present in over 90% of the neurologically normal infants by 35 to 36 weeks gestational age (GA), but a large proportion of infants with intraventricular haemorrhage (IVH) manifested immature flash-VEP waveforms. The authors concluded that the extent of delay in the maturation of the VEP was related to the degree of neurological insult.…”
mentioning
confidence: 99%
“…De Vries et al [42] and Eken et al [43] found that infants with extensive cystic PVL often manifested abnormal VEP with poor-quality waveforms; a reproducible response could rarely be elicited in infants with subcortical lesions. Severe visual impairment was invariably present in infants in whom VEP could not be recorded [41][42][43]. Contrary findings have been reported by Ekert et al [44] who recorded VEP in the first and second weeks of life in 45 preterm infants.…”
Section: Discussionmentioning
confidence: 69%
“…Placzek at al. [41] recorded VEP in 70 premature infants, 26 of whom had IVH. A large proportion of infants with IVH manifested abnormal VEP.…”
Section: Discussionmentioning
confidence: 99%
“…VEP is particularly useful to investigate the functional integrity of the visual system of high-risk infants where obvious retinal and neurological abnormalities are not observed [10]. Several flash VEP studies of high-risk infants are available in the literature [11][12][13][14][15]. These studies have demonstrated that immature P2 waveform [11], irreproducible waveform responses, and unrecordable VEP measurements [13] are associated with abnormal neurodevelopment [12] and visual impairment in pre-term infants.…”
Section: Introductionmentioning
confidence: 99%
“…Several flash VEP studies of high-risk infants are available in the literature [11][12][13][14][15]. These studies have demonstrated that immature P2 waveform [11], irreproducible waveform responses, and unrecordable VEP measurements [13] are associated with abnormal neurodevelopment [12] and visual impairment in pre-term infants. VEP has also been investigated for its prognostic value of long-term visual and neurodevelopmental outcomes in infants [16][17][18] but the results are ambiguous.…”
Section: Introductionmentioning
confidence: 99%